The long arm of the gang: Disengagement under gang governance in Central America - Cruz, José Miguel (Criminology, 2023)
Institutionalized gangs are youth groups that have developed the ability to persist, expand, and restructure organizationally around criminal activities and have imposed their norms and behavioral prescriptions on the communities where they operate. So how does a gang member manage to leave these groups and abandon violent crime? This article proposes a new theoretical model of gang disengagement based on a comparative case study with MS-13 and Barrio 18 gangs in Central America. It is based on 112 in-depth interviews with former gang members in El Salvador, Guatemala, and Honduras. The article identifies three forms of gang disengagement: religious conversion, secular pass, and walking away. Two factors, the gang's organizational structure and its territorial reach, mediate in the choices gang members have when leaving an institutionalized gang. The specific combination of these factors makes some disengagement modes more likely than others. The article underscores the role of gang governance in shaping gang members’ disengagement processes.